Highly efficient H2S scavengers via thiolysis of positively-charged NBD amines. Issue 30 (14th July 2020) - Ismail, Ismail; Chen, Zhuoyue; Sun, Lu; Ji, Xiuru; Ye, Haishun; Kang, Xueying; Huang, Haojie; Song, Haibin; Bolton, Sarah G.; Xi, Zhen; Pluth, Michael D.; Yi, Long
Abstract : We demonstrate that positively-charged NBD amines can effectively scavenge biological H2 S in live cells and in mice. Abstract : H2 S is a well-known toxic gas and also a gaseous signaling molecule involved in many biological processes. Advanced chemical tools that can regulate H2 S levels in vivo are useful for understanding H2 S biology as well as its potential therapeutic effects. To this end, we have developed a series of 7-nitro-1, 2, 3-benzoxadiazole (NBD) amines as potential H2 S scavengers. The kinetic studies of thiolysis reactions revealed that incorporation of positively-charged groups onto the NBD amines greatly increased the rate of the H2 S-specific thiolysis reaction. We demonstrate that these reactions proceed effectively, with second order rate constants ( k 2 ) of >116 M −1 s −1 at 37 °C for NBD-S8 . Additionally, we demonstrate that NBD-S8 can effectively scavenge enzymatically-produced and endogenous H2 S in live cells. Furthering the biological significance, we demonstrate NBD-S8 mediates scavenging of H2 S in mice.